2020
DOI: 10.5114/wo.2020.102671
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-pathological and prognostic implications of Srx, Nrf2, and PROX1 expression in gastric cancer and adjacent non-neoplastic mucosa – an immunohistochemical study

Abstract: Introduction: Sulfiredoxin (Srx), which is an endogenous antioxidant substance which could, regulate the signaling pathways of reactive oxygen species. Nuclear factor erythroid 2-related factor 2 (Nrf2) is Cap-N-collar (CNC) transcription factors family member that have essential roles in regulation of antioxidant response. The transcription factor PROX1 is a transcription factor and a key regulatory protein in cancer development. Aim of the study: To analyze levels of tissue expression of Srx, Nrf2, and PROX1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 41 publications
2
4
1
Order By: Relevance
“…Several studies support the correlation between high expression of PROX1 and shorter OS in GC patients (15)(16). But the other studies reported a total of 598 patients nding that PROX1 overexpression is associated with a longer OS (11)(12)(13). However, our meta-analysis reveals that PROX1 expression is not related with OS at 1, 3, or 5 years.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Several studies support the correlation between high expression of PROX1 and shorter OS in GC patients (15)(16). But the other studies reported a total of 598 patients nding that PROX1 overexpression is associated with a longer OS (11)(12)(13). However, our meta-analysis reveals that PROX1 expression is not related with OS at 1, 3, or 5 years.…”
Section: Discussioncontrasting
confidence: 69%
“…(16). According to Abeer M. Hafez et al (13) and KOJI UETA et al ( 16), PROX1 expression acts as a good prognostic predictor for GC patients. But Ueta K et al reported that PROX1 may be a bad promising prognostic biomarker (9).…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of PROX1 in GC is controversial. Hafez AM et al also reported that high expression of PROX1 is relevant, but oppositely, to pathological stage, lymphatic metastasis and T stage [ 12 ]. Kasurinen A et al reported that the expression of PROX1 is not statistically correlated with the depth of invasion, lymph node metastasis and cancer stage by their study [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, Alli Laitinen et al [ 10 ] reported that the high expression of PROX1 is irrelevant to pathological stage, lymphatic metastasis, T stage, and is correlated with a good prognosis. Hafez AM et al also reported that high expression of PROX1 is correlated with good prognosis but relevant to pathological stage, lymphatic metastasis and T stage [ 12 ]. The relationship between PROX1 expression and clinicopathological characteristics and prognosis in GC are widely disputed and remain controversial.…”
Section: Introductionmentioning
confidence: 99%
“…There is no certainty regarding the significance of PROX1 expression in GC. While there are reports that PROX1 expression was a poor prognostic factor [8][9][10], there are various reports that it correlated with a good prognosis [11][12][13] or was not a prognostic factor [14]. The purpose of this study was to investigate and clarify whether PROX1 is a prognostic factor in GC.…”
Section: Introductionmentioning
confidence: 99%